INNOVATING STATE FINANCIAL OVERSIGHT: INSIGHTS FROM FOREIGN EXPERIENCES - Yarkulova Marifat; Jurayeva Dildora Mansur kizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract: This article explores the innovation of state financial oversight through the integration of successful foreign practices. By analyzing various international audit frameworks and financial control mechanisms, it identifies key strategies that enhance transparency, accountability, and efficiency in public finance management. The study highlights case examples from several countries, illustrating how adaptive approaches can address common challenges in state financial oversight. Ultimately, this research aims to provide actionable recommendations for policymakers seeking to improve their financial governance systems by learning from global experiences.